Exploring how the Kidney BEAM physical activity digital health intervention improved mental health-related quality of life for people living with kidney disease: a mixed methods approach - Castle, Ellen; Billany, Roseanne E.; Young, Hannah M. L.; Walklin, Christy; Briggs, Juliet; Asgari, Elham; Bhandari, Sunil; Burton, James O.; Bramham, Kate; Deelchand, Vashist; Hamilton, Alexander; Jesky, Mark; et al. (Elsevier, 2024)
Introduction: The Kidney BEAM randomized controlled trial reported clinically meaningful and statistically significant improvements in mental health-related quality of life (HRQoL), physical function (sit-to-stand 60, but not the physical component of HRQoL) and patient activation after a 12-week physical activity digital health intervention (DHI). This study explores factors that contributed to the effectiveness of Kidney BEAM through mixed methods analyses. Methods: Quantitative data analysis was obtained from the recently published primary manuscript. Par ticipants from the Kidney BEAM trial intervention group (n ¼ 30) completed individualized semistructured interviews after the 12-week DHI. Interviews were analyzed using the framework method with inductive and deductive coding. Quantitative and qualitative data collection and analyses occurred concurrently, and independently, before combining using a mixed methods analysis with joint displays to triangulate datasets and further explore the primary findings. Results: The integrated mixed methods analyses facilitated explanation of the primary findings. The Kidney BEAM intervention was shown to have mental and physical wellbeing benefits and enhanced self management in this cohort of people living with chronic kidney disease (CKD). Elements that contributed to the effectiveness of the intervention were reported, including the different functional levels and gradual progression of the program, shared lived experiences with other participants, self-monitoring, the sense of achievement, taking back control of their health, moving beyond medications, and feeling safe and confident to exercise. Conclusion: Elements of the Kidney BEAM intervention that contributed to the main quantitative trial findings were identified. This will allow researchers and practitioners to maximize the effectiveness of DHIs to enhance healthy behaviors in people living with CKD.